A practical technique for hydrodynamic coefficients modification in SHEAR7 for fatigue assessment of riser buoyancy modules under vortex-induced vibration - Lekkala, M.R. (Elsevier Ltd, 2020)
The hydrodynamic coefficients in semi-empirical tool are optimized for a riser attached with staggered buoyancy modules undergoing Vortex-Induced Vibration (VIV) based on the SHELL Oil Experiment. The existing prediction tools are based on data derived from experiments, number of assumptions from strip theory, energy balance between fluid and structure and use of lift coefficient databases. Current advancements in conducting and calculating VIV response from the experiments shows that these assumptions may be invalid. The major difference arises between experimental observations and theoretical estimations is from lift coefficient databases. The databases extracted under laboratory conditions have limited Reynolds number flow conditions and only cross-flow motions were considered. The extracted hydrodynamic excitation coefficient database is posed to optimization problem, where the main objective is to minimize the prediction error of semi-empirical tools when compared with experimental results. We optimize the existing excitation coefficient database to improve the fatigue damage prediction of riser attached with staggered buoyancy modules. Application of modification factors and optimizing the hydrodynamic lift coefficients to the data from SHELL Exploration and Production Test provides the new optimized excitation coefficient datasets which reduce the error in the predicting the VIV response of the riser with staggered buoyancy modules. Â© 2020 Elsevier Ltd